Investigation of lignin as an alternative extender of bitumen for asphalt pavements. (10th February 2021) - Wu, Jiantao; Liu, Quan; Wang, Chonghui; Wu, Wenjuan; Han, Weipeng
Abstract: Using alternative extender as a substitute for bitumen is one of the most effective approaches to construct asphalt pavements. In this study, the feasibility of using lignin as an extender for bitumen was investigated. According to the literature review and preliminary tests, the ratio of bitumen to lignin was fixed at 4:1 by mass. The viscosity measurement determined the workability of lignin modified bitumen (LMB). Rheological properties in a broader temperature range were investigated through the dynamic shear rheometer (DSR) and bending beam rheometer (BBR). The anti-aging performance of LMB was estimated by employing the thin-film oven test (TFOT) and Fourier Transform Infrared Spectroscopy (FTIR). Besides, the storage stability of LMB was discussed in terms of morphology, lignin concentration, and mechanical properties. Lastly, the thermal stability of LMB was examined to eliminate the safety concern in construction. The results indicated that lignin showed explicit chemical activities (associated hydroxyl –OH and carbonyl groups –CO), which significantly affected the bitumen properties from varying perspectives. The stiffness of bitumen increased, and the temperature susceptibility of bitumen was reduced after the incorporation of lignin. Meanwhile, the mixing and paving temperatures for the pavement construction increased by over 10 °C. The presence of abundant associated hydroxyl in lignin was the primary factor that changes the anti-aging capacity of bitumen. The problem of lignin segregation was reasonably serious but was solved by adding additives. In general, the lignin could be a decent extender for bitumen with the appropriate procedure in practice. Graphical abstract: Image 1 Highlights: The incorporation of lignin in bitumen enhances the bitumen stiffness but requires more energy consumption. Storage stability of lignin modified bitumen can be significantly improved by the Polyethylene glycol. Chemical functional groups such as the associated hydroxyl in lignin improve the aging resistance of bitumen.